Us Foreign Policy After The Cold War : Global Hegemon Or Reluctant Sheriff?. - Cameron, Fraser, 1947- (Taylor & Francis Ltd., 2005)
Suitable for those studying American Politics or International Relations, this fully updated textbook looks at the last two and a half years in American politics, including the 2004 presidential election campaign and examining foreign policy.